2017
DOI: 10.1177/0885066617709434
|View full text |Cite
|
Sign up to set email alerts
|

Predictors to Intravenous Fluid Responsiveness

Abstract: Management with intravenous fluids can improve cardiac output in some surgical patients. Management with static preload indicators, such as central venous pressure and pulmonary artery occlusion pressure, has not demonstrated a suitable relationship with changes in the cardiac output induced by intravenous fluid therapy. Dynamic indicators, such as the variability of arterial pulse pressure or stroke volume variation, have demonstrated a suitable relationship. Since improvement in cardiac output does not guara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 142 publications
0
19
0
Order By: Relevance
“…In the parameters predicting fluid responsiveness, it was shown that dynamic indicators (SVV and PPV) had more precise diagnostic value than did static indicators (central venous pressure and pulmonary artery wedge pressure) [ 5 ]. In a related meta-analysis, the results were similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the parameters predicting fluid responsiveness, it was shown that dynamic indicators (SVV and PPV) had more precise diagnostic value than did static indicators (central venous pressure and pulmonary artery wedge pressure) [ 5 ]. In a related meta-analysis, the results were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Static indicators (central venous pressure or pulmonary artery wedge pressure) are not recommended as good diagnostic indexes [ 3 , 4 ]. Some dynamic indicators, such as stroke volume variation (SVV) and pulse pressure variation (PPV), have better diagnostic value for predicting fluid responsiveness [ 5 ]. However, it is necessary for physicians to perform invasive vessel puncturing to monitor PPV or SVV.…”
Section: Introductionmentioning
confidence: 99%
“…Static measures of fluid responsiveness such as right ventricular end-diastolic volume, left ventricular end-diastolic volume, central venous pressure, and pulmonary artery occlusion pressure are no longer routinely recommended to guide or assess response to intravenous fluid therapy. 40 Dynamic measures such as stroke volume variation, pulse pressure variation, and inferior vena cava collapsibility are better able to predict fluid responsiveness. 40 Effectiveness of intravenous fluid therapy is frequently defined as an increase in blood pressure or cardiac output, and the degree and rapidity of the desired increase is patient specific.…”
Section: Monitoring Fluid Therapymentioning
confidence: 99%
“…40 Dynamic measures such as stroke volume variation, pulse pressure variation, and inferior vena cava collapsibility are better able to predict fluid responsiveness. 40 Effectiveness of intravenous fluid therapy is frequently defined as an increase in blood pressure or cardiac output, and the degree and rapidity of the desired increase is patient specific. Additionally, increases in urine output to greater than 0.5 mL/kg/h or decreases in lactate level may indicate that a patient is responding appropriately to intravenous fluid therapy.…”
Section: Monitoring Fluid Therapymentioning
confidence: 99%
“…One hard lesson learned from the experience with invasive central venous and PAC is that using static assessments and/or filling pressures to predict fluid responsiveness has been unsatisfactory. 7 Several factors other than fluid derangements have been associated with abnormal filling pressures and/or cardiac dimensions such as altered ventricular compliance and valvular heart disease. Static measurements, whether pressure based from PAC or dimensional from echocardiography, all share these liabilities.…”
mentioning
confidence: 99%